Utilization of Biomass from Kerai Payung Trees and Waste Paper Through Pyrolysis Technology to Support the Zero-Waste Concept - Indadari, Anggita Putri; Anisa, Nurfa; Santoso, Asih Budi (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Wisnuwardhana University is a private institution with a green campus environment surrounded by Kerai Payung trees. This environment produces organic waste from trees and inorganic waste such as used paper from campus activities. This study aims to achieve zero-waste processing by using pyrolysis technology to process campus waste, ensuring minimal residue. The experimental method involves comparing waste processing outcomes between conventional combustion and pyrolysis, the data was analyzed by comparing the results of pyrolysis with conventional combustion. The results of biochar from the pyrolysis process of used paper, Kerai Payung leaves, and nagging Kerai Payung tree are 76 g, 250 g, and 26 g. Then the results of ash from the pyrolysis process of used paper, Kerai Payung tree leaves, and nagging Kerai Payung tree are 23 g, 49 g, and 23 g. The results of liquid smoke from the pyrolysis process of used paper, Kerai Payung tree leaves, and nagging Kerai Payung tree are 75 mL, 50 mL, and 10 mL. Conventional combustion does not produce liquid smoke because the smoke from combustion is left to decompose in the air. This finding shows that pyrolysis is more effective than conventional combustion, because pyrolysis converts smoke into liquid, thereby reducing air pollution. In addition, the biochar and liquid smoke produced can be useful for agriculture and act as food preservatives, thus supporting sustainable waste management on campus.